Testicular Mass in Children: A Case Report - Shah, Brijesh Kumar; Thapa, Bijay; Thapa Basnet, Anupama (Nepalese Medical Journal, 2024)
Testicular sarcomas constitute only 1–2% of all testicular tumors and are mostly associated with germ cell tumors. Primary intratesticular localization is very rare and must be differentiated from paratesticular locations. Accurate diagnosis and early treatment are essential as it is an aggressive tumor with high metastatic potential and poor prognosis. The optimal treatment is based on radical inguinal orchidectomy and chemotherapy.